(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Objectives To study the knowledge, attitude, perception and practices (KAP) of medical students regarding antimicrobial resistance (AMR) and usage Methods A cross sectional questionnaire based survey among second and third year medical students of a teaching hospital was conducted, whereby their KAP regarding antibiotic use and resistance was assessed by using five point likert scale whose responses ranged from “strongly agree” to “strongly disagree,” always” to “never” and “very important” to “unimportant”. Data was analyzed using simple descriptive statistics Observations The response rate was 100% among the 150 students who were asked to participate in the survey. The number of respondents who agreed that antibiotic resistance is an important and serious public health issue in their hospital is (n=114, 76%). Majority, 94% (n=141) were aware that bacteria are not responsible for causing colds and flu. Among the factors which govern their choice/selection of an antibiotic, the ability of the antibiotic to promote resistance was rated as the most important factor by 95% (n=143) of them. Antibiotic cost was considered as important by only 52% (n=78) of the respondents. Conclusion The data obtained can help us arrive at a conclusion with respect to the educational needs of the students regarding antibiotic resistance and the aspects which are deserving of our attention and requiring suitable educational interventions.